2020
DOI: 10.16882/hortis.823968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Rootstocks on Storage Life and Quality of Loquat Fruit (cv. Gold Nugget)

Abstract: In this study, the effects of rootstocks on storage life and quality in Gold Nugget loquat grafted on quince, hawthorn and loquat rootstocks were investigated. After harvest, fruit were placed in plastic boxes (2 kg) covered with stretch film and stored for 45 days at 5 ± 0.5°C and 90 ± 5% RH. Weight loss, fruit firmness, total soluble solid, titratable acidity, maturity rate, respiration rate, ethylene production, CO2 and O2 concentrations in package, skin colour (L*,a*,b*,C*,h°), decay rate and sensory quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…After obtaining substantial yield, proper post-harvest storage of peach fruit is necessary to increase the storage life for extended/distant market availability. The findings of other researchers ( Tepe and Koyuncu, 2020 ) also support the contention regarding great influence of rootstocks on scion cultivar for storage and quality parameters. Reig et al (2020) also reported that appropriate rootstock selection is very important for establishment of an orchard.…”
Section: Introductionsupporting
confidence: 74%
“…After obtaining substantial yield, proper post-harvest storage of peach fruit is necessary to increase the storage life for extended/distant market availability. The findings of other researchers ( Tepe and Koyuncu, 2020 ) also support the contention regarding great influence of rootstocks on scion cultivar for storage and quality parameters. Reig et al (2020) also reported that appropriate rootstock selection is very important for establishment of an orchard.…”
Section: Introductionsupporting
confidence: 74%
“…For the objective of preserving and maintaining the quality of the fruits, effective preservation methods must be established in order to increase the shelf life of loquat (Figure 3). fruit's quality and give buyers a superior quality product (Seyla & Koyuncu, 2020). Cold storage is a practical method for extending the shelf life of loquat fruit after harvest (Hou et al, 2021).…”
Section: Postharvest Storage and Preservation Technologymentioning
confidence: 99%
“…Temperature is one of the most significant factor which may affect the storage time. The cold storage method is utilized to preserve the fruit's quality and give buyers a superior quality product (Seyla & Koyuncu, 2020). Cold storage is a practical method for extending the shelf life of loquat fruit after harvest (Hou et al, 2021).…”
Section: Postharvest Storage and Preservation Technologymentioning
confidence: 99%
See 1 more Smart Citation